Alternative donor hematopoietic stem cell transplantation for sickle cell disease - Andrew L. Gilman; Michael J. Eckrich; Stacy Epstein; Carrie Barnhart; Mark Cannon; Tracy Fukes; Michelle Hyland; Krishna Shah; Darci Grochowski; Elizabeth Champion; Anastasia Ivanova (Blood Advances, 2017)
Abstract: Most patients who could be cured of sickle cell disease (SCD) with stem cell transplantation do not have a matched sibling donor. Successful use of alternative donors, including mismatched family members, could provide a donor for almost all patients with SCD. The use of a reduced-intensity conditioning regimen may decrease late adverse effects. Ten patients with symptomatic SCD underwent CD34+ cell-selected, T-cell–depleted peripheral blood stem cell transplantation from a mismatched family member or unrelated donor. A reduced-intensity conditioning regimen including melphalan, thiotepa, fludarabine, and rabbit anti-thymocyte globulin was used. Patients were screened for a companion study for immune reconstitution that included a donor lymphocyte infusion given 30-42 days after transplant with intravenous methotrexate as graft-versus-host disease (GVHD) prophylaxis. Seven eligible patients were treated on the companion study. Nine of 10 patients are alive with a median follow-up of 49 months (range, 14-60 months). Surviving patients have stable donor hematopoietic engraftment (mean donor chimerism, 99.1% ± 0.7%). There were no sickle cell complications after transplant. Two patients had grade II-IV acute GVHD. One patient had chronic GVHD. Epstein-Barr virus–related posttransplant lymphoproliferative disorder (PTLD) occurred in 3 patients, and 1 patient died as a consequence of treatment of PTLD. Two-year overall survival was 90%, and event-free survival was 80%. A reduced-intensity conditioning regimen followed by CD34+ cell-selected, T-cell–depleted alternative donor peripheral blood stem cell transplantation achieved primary engraftment in all patients with a low incidence of GVHD, although PTLD was problematic. This trial was registered at clinicaltrials.gov as #NCT00968864.